PENERAPAN ALGORITMA A-STAR PADA APLIKASI PENCARIAN LOKASI FOTO BERBASIS ANDROID - M Ativ Mutsakov (Balitbangda Provinsi Lampung, 2020)
Abstract: The art of photography continues to develop over time, a rapidly growing development has an impact on the high interest of the community in the world of photography. Many of them make photography as a form of media for creativity or hobbies and there are those who make it as a place to earn income. But not a few of these photographers who do not know some of the spots or locations of photos in the city of Bandar Lampung, which has aesthetic value when combined with the concept presented. Information limitations in the form of access routes or roads that can be taken to the location are also an important highlight. With this, the effort of that matter is by utilizing the development of information technology, to make an application that will help the community in finding the desired location or spot for photos. The results of this study in the form of an application that can provide information about the spot or location of photos in the city of Bandar Lampung, which is equipped with a guide in the form of maps that have been given the A-Star algorithm to determine the nearest route to the location or photo spot.